2012
DOI: 10.3109/09513590.2012.705387
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor C enhances cervical cancer migration and invasion via activation of focal adhesion kinase

Abstract: Vascular endothelial growth factor C (VEGF-C) is correlated positively with clinical cervical cancer metastasis and survival. Previously we showed that VEGF-C directly activated actin-binding protein moesin, leading to the formation of membrane protrusions. However, whether VEGF-C alters cervical cancer cell adhesion to the extra-cellular matrix is currently unknown. In this study, we investigated the effects of VEGF-C on the formation of focal adhesion complexes, which provide anchoring sites for cell attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Anti-VEGF treatment augments the tumor radiation response under normoxic or hypoxic conditions, which is a novel therapeutic strategy in cervical cancer (37). VEGFA and VEGFC, two members of the VEGF family, were recently identified as the predominant tumor metastasis-driving factors in various human cancers types, including renal cell carcinoma (38), hepatocellular carcinoma (39) and cervical cancer (40)(41)(42). The present study identified VEGFA and VEGFC as targets of miR-144 via directly binding to the 3'-UTRs of VEGFA and VEGFC mRNA in a dual luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF treatment augments the tumor radiation response under normoxic or hypoxic conditions, which is a novel therapeutic strategy in cervical cancer (37). VEGFA and VEGFC, two members of the VEGF family, were recently identified as the predominant tumor metastasis-driving factors in various human cancers types, including renal cell carcinoma (38), hepatocellular carcinoma (39) and cervical cancer (40)(41)(42). The present study identified VEGFA and VEGFC as targets of miR-144 via directly binding to the 3'-UTRs of VEGFA and VEGFC mRNA in a dual luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has identified molecular mechanisms involved in cervical cancer. Molecules such as vascular endothelial growth factor-C (VEGF-C) (8), Src homology-2 domain containing protein, tyrosine phosphatase-2 (SHP-2) (9), or CD147 isoform-4 (CD147-4) (10) are known to promote the proliferation, migration or invasion of cervical cancers by activating focal adhesion kinases (8), through inhibition of interferon-β production (9), or with an upregulated expression of the cancerous inhibitors PP2A (CIP2A), polo-like kinase (PLK) and cyclin D1 but a downregulated p27 expression (10). By contrast, tumor-suppressive molecules, such as Beclin1 (11) and histone deacetylase (HDAC) 10 (12) have been confirmed to inhibit the invasion and migration of cervical cancer cells by decreasing the expression of VEGF and matrix metalloproteinase (MMP)-9 proteins (11), or through the inhibition of MMP-2 and -9 expression (12).…”
Section: Introductionmentioning
confidence: 99%
“…Filamin-C ( FLNC ) was associated with the risk of glioblastoma multiforme ( 19 ). Vascular endothelial growth factor receptor 3 ( FLT4 ) enhances cervical cancer migration and invasion ( 20 ). Hepatocyte growth factor ( HGF ) increased cisplatin resistance through downregulation of AIF in lung cancer ( 21 ).…”
Section: Discussionmentioning
confidence: 99%